Features of cognitive functions in patients with arterial hypertension with the presence / absence of chronic heart failure - Yusupova Kh.F; Radjabova G.M; Abdullaeva G.Zh; hamidullayeva G.A (Peerian Journals Publishing, 2022)
To assess the state of cognitive functions in patients with arterial hypertension (AH) with the presence / absence of chronic heart failure (CHF).
Keywords: absence; patients; hypertension